Actual evapotranspiration and crop coefficients of irrigated lowland rice (Oryza sativa L.) under semiarid climate - Djaman, Koffi; Rudnick, Daran R.; Moukoumbi, Yonnelle D.; Sow, Abdoulaye; Irmak, Suat (Italian Journal of Agronomy, 2019)
Lowland irrigated rice is the predominant crop produced in the Senegal River Valley characterised by very low annual rainfall, high temperatures, and low relative humidity. The Senegal River is shared by Senegal, Mali, Mauritania, and Guinea, and serves as the main source of irrigation water for the adopted double rice cropping system. Developing appropriate resource management strategies might be the key factor for the sustainability of rice production in the region. This study aims to estimate rice seasonal evapotranspiration (ETa), irrigation water requirement, and to develop rice growth stage specific crop coefficients (Kc) to improve rice water productivity. Field experiments were conducted during the hot and dry seasons in 2014 and 2015 at the AfricaRice research station at Fanaye in Senegal. Irrigation water inputs were monitored and actual crop evapotranspiration was derived using the water balance method. Daily reference evapotranspiration (ETo) was estimated using the Penman-Monteith equation and the weather variables were collected at the site by an automated weather station. The results showed that the ETo during the hot and dry season from February 15th to June 30th varied from 4.5 to 9.9 mm and from 3.7 to 10.8 mm in 2014 and 2015, respectively, and averaged 6.8 mm d–1 in 2014 and 6.6 mm d–1 in 2015. The seasonal irrigation water amount for the transplanted rice was 1110 mm in 2014 and 1095 mm in 2015. Rice daily ETa varied from 4.7 to 10.5 mm in 2014 and from 4.4 to 10.5 mm in 2015 and averaged 8.17 mm in 2014 and 8.14 mm in 2015. Rice seasonal ETa was 841.5 mm in 2014 and 855.4 mm in 2015. The derived rice Kc values varied from 0.77 to 1.51 in 2014 and 0.85 to 1.50 in 2015. Rice Kc values averaged 1.01, 1.31, and 1.12 for the crop development, mid-season and late season growth stages, respectively. The Kc values developed in this study could be used for water management under rice production during the hot and dry season in the Senegal River Valley.